Розвиток гендерного бюджетування в Україні у контексті євроінтеграції - Глущенко, Ольга Вікторівна; Стеценко , Тетяна Володимирівна; Hlushchenko, Olha; Stetsenko, Tetiana (Київ : ДКС Центр, 2024)
У статті на теоретичному рівні встановлено взаємозв'язок між етапами бюджетного процесу та гендерною відповідальністю, розроблено дорожню карту (Road Map) гендерного бюджетування. Запропонована дорожня карта гендерного бюджетування робить рівнозначними бюджетний та гендерний процеси. Розробка дорожньої карті гендерного бюджетування як єдиної сукупності взаємопов'язаних правил та процедур, що дають змогу здійснити фінансування гендерночутливих проєктів та досягнути заплановані результати. Значення запропонованої розробки полягає у рівноправному поєднанні фінансових та гендерних компонент, виструнчення їх у ланцюг послідовних кроків, що дозволяють досягти мети фінансування гендерночутливого проєкту та проконтролювати як гендерну так і фінансову компоненти. Удосконалено методичних підхід до технології гендерного бюджетування, що дозволяє перейти від мультидисциплінарної розпорошеності до синергетичного ефекту, який підсилить науково-практичний результат процесу гендерного бюджетування в Україні.

The study, based on the content analysis of Ukrainian and foreign publications on gender budgeting, classified the works of Ukrainian scientists and found that the topic of gender budgeting is gaining popularity and scientific dissemination among young authors who are carriers of the values of European integration. The scientific research of mature scientists is a driver of change in the minds of not only young people but also the whole society. It has been established that all domestic scientific developments lack one thing — the analysis of specific cases from the Ukrainian experience: from gender analysis, through open dialogue with the community, justification of gender sensitive projects, preparation of budget requests, receipt of funds to project implementation and reporting. There is no full description of the project from the initial to the final stage, which indicates certain gaps in both theoretical and practical activities. It is emphasised that the key to the successful creation and implementation of gendersensitive projects is the institutionalisation of gender statistics at the level of the State Statistics Service of Ukraine. So far, gender statistics in Ukraine are scattered among a number of official and unofficial websites. The article establishes the relationship between the stages of the budget process and gender responsibility at the theoretical level and develops a roadmap for gender budgeting. The proposed gender budgeting roadmap makes the budget and gender processes equivalent. Development of a gender budgeting roadmap as a single set of interrelated rules and procedures that allow financing gendersensitive projects and achieving the planned results. The significance of the proposed development lies in the equal combination of financial and gender components, lining them up in a chain of sequential steps that allow achieving the goal of financing a gendersensitive project and controlling both gender and financial components. The methodological approach to the gender budgeting technology has been improved, which allows to move from multidisciplinary fragmentation to a synergistic effect that will enhance the scientific and practical results of the gender budgeting process in Ukraine.
Gender budgeting in Ukraine in the context of europeanintegratio
Keywords: SOCIAL SCIENCES::Business and economics; гендерне бюджетування; сталий розвиток; gender budgeting; sustainable development; бюджет; місцеві фінанси; запити громади; budget; local finance; community demands